Efeitos da carbamilação in vitro sobre a quantificação da albumina pelos ensaios imunoturbidimétrico e colorimétrico - Cassol, José Pedro Etchepare (2021)
Albumin is a low-molecular-weight non-glycosylated globular protein with several functions, such as maintaining colloidal osmotic pressure and transporting various substances. It is the main protein present in plasma. Plasma albumin is decreased in several clinical situations, including situations associated with the loss of albumin in the urine, known as albuminuria. Usually, a significant amount of albumin filtered by the glomerulus is reabsorbed by the proximal convoluted tubules, and only a concentration below 30 mg/24h is found in urine samples. Additionally, serum albumin has a reference value between 3.5-5.2 g/dL. Several methods are available for quantifying albumin in serum and urine samples. In clinical practice, colorimetric assays measure serum protein, while immunological methods are employed to quantify albumin in the urine. Diseases that affect the kidneys, such as chronic kidney disease, affect albumin concentrations in serum and urine. Therefore, this protein is a biomarker for investigating some disorders. In addition, kidney pathologies may impair urine production and promote the accumulation of substances in the blood, such as urea. Urea is degraded into ammonia and cyanate, which is responsible for the protein carbamylation process. This non-enzymatic post-translational modification cause changes in albumin properties and functions, which accelerate molecular aging through the formation of carbamyl groups. No studies assessed the interference of albumin carbamylation in urinary concentrations measured by the immunoturbidimetric method. Besides, no studies analyzed the impact of this process in the colorimetric method used to quantify albumin at levels compatible with normality and hypo and hyperalbuminemia. Therefore, this study aimed to evaluate the interference of albumin carbamylation on immunoturbidimetric and colorimetric assays used to measure this protein in urine and serum samples, respectively. Human albumin solutions were prepared at concentrations suitable for assay by the respective methods in PBS 0.1 mol/L pH 7.4. In vitro induction of carbamylation occurred by using six different concentrations of potassium cyanate (in millimolar concentrations), already well characterized in previous studies. The solutions were incubated in microtubes for 48h at 37°C. After the established time, the samples were analyzed in an automated clinical biochemistry analyzer BS380 using commercially available immunoturbidimetric and colorimetric assays. The addition of increasing concentrations of potassium cyanate led to a significant underestimation (p<0.001) of albumin levels, both urinary measured by immunoturbidimetry (9.7-24.0%), as well as serum albumin measured by colorimetric assay (13.4-27.3%). Therefore, adding a carbamylating agent at different concentrations over albumin solutions caused an underestimation of the results measured by both techniques. These findings may be related to changes in the molecules caused by carbamylation, which modify the binding with the specific antibody in the immunoturbidimetric assay and the binding ability with ligands in the colorimetric assay.